An RFC4/Notch1 signaling feedback loop promotes NSCLC metastasis and stemness - Lei Liu (Nature Portfolio, 2021)
Activated Notch signalling promotes cancer metastasis and stemness. Here the authors show that Notch1 activates transcription of DNA replication factor RCF4 and that RCF4 binds and stabilises Notch1 intracellular domain (NICD1) to promote cancer metastasis.